Green Recovery with Resilience and High Quality Development CCICED Annual Policy Report 2021. (Springer Nature Singapore : Imprint: Springer, 2023)
This open access book is based on the research outputs of China Council for International Cooperation on Environment and Development (CCICED) in 2021. It covers major topics of Chinese and international attention regarding green development, such as climate, biodiversity, ocean, BRI, urbanization, sustainable production and consumption, technology, finance, value chain, and related topics. It also reviews the progress of China's environmental and development policies and the impacts from CCICED. This is a highly informative and carefully presented book, providing insight for policy makers in environmental issues.